LITERASI MEDIA SEBAGAI MANAJEMEN KONFLIK KEAGAMAAN DI INDONESIA - Anisa Setya Arifina (Universitas Tidar, 2017)
Judging from the social situation in Indonesia, horizontal conflict with religious sentiment was escalated since Pilkada that was held simultaneously on February 15, 2017. The issue of alleged blasphemy of Islam by Ahok rolling the snowball effect of politics that could threaten national security. The use of social media is escorted by the government through the Electronic Information and Transaction Act (UU ITE). Religious conflict management is also supported by all stakeholders including netizens who are expected to be able to use social media wisely and responsible for what they are disseminating and not easily provoked by information spread across social media.